2021
DOI: 10.5539/ies.v14n6p103
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Skills and Self-Control as Predictors of Resilience in Teachers Candidates

Abstract: This research aims to examine how emotion regulation skills and self-control variables influence teacher candidates’ levels of resilience. The research was conducted based on the relational screening model. The research group consisted of a total of 462 students, 225 (48.7%) boys and 237 (51.3%) girls, studying at Afyon Kocatepe University Faculty of Education in the 2020-2021 academic year. The average age of the research group was 20.23. “Personal Information Form”, “B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…In this regard, it is conceivable to propose that individuals who exhibit high levels of self-control may be more resilient during times of difficulties and, as a result, better preserve their mental health. Additionally, numerous studies showed that self-control positively predicts resilience (Artuch-Garde et al, 2017;Sagar, 2021;Yang et al, 2019). Experimental research by Morrison and Pidgeon (2017) demonstrated that willpower exercises improve resilience and self-control as well as decrease mental health issues among college students.…”
Section: Mediating Role Of Resiliencementioning
confidence: 99%
“…In this regard, it is conceivable to propose that individuals who exhibit high levels of self-control may be more resilient during times of difficulties and, as a result, better preserve their mental health. Additionally, numerous studies showed that self-control positively predicts resilience (Artuch-Garde et al, 2017;Sagar, 2021;Yang et al, 2019). Experimental research by Morrison and Pidgeon (2017) demonstrated that willpower exercises improve resilience and self-control as well as decrease mental health issues among college students.…”
Section: Mediating Role Of Resiliencementioning
confidence: 99%